Theoretical framework of augmented reality, virtual reality and artificial intelligence: Uses in education and other activities - Villalobos López, José Antonio (Emerging Trends in Education, 2024)
The article presented follows the deductive method, with a hermeneutic paradigm and a qualitative approach. The aim is to highlight the theoretical framework of three of the emerging or disruptive technologies (augmented and virtual reality, and artificial intelligence) and their use mainly in the educational sector and in other economic activities. The purpose of augmented reality is to incorporate digital information (images, video and audio) into the real world, while virtual reality allows users to enter an alternative world through immersion, which is simulated by a computer or other device. In addition to the educational field, its applications are in commerce, health, tourism, leisure and entertainment, and the defense sector. Artificial intelligence (AI) is increasingly present in daily and everyday activities. AI is the use of systems with a certain degree of autonomy, which seeks to emulate human behavior, using algorithms to achieve specific objectives or solve problems. In the educational field, AI can be applied from elementary to postgraduate level, because if integrated with active learning methodologies, it can generate an improvement and interest among students.